Análise das normas de acessibilidade no transporte aéreo: uma discussão por meio da metassíntese qualitativa do conceito de pessoa com deficiência e da acessibilidade - Nasser, Henrique Sacomano (Universidade Federal de São Carlos, 2022)
The use of airport environments by passengers with disabilities has been increasing both in Brazil and worldwide. The process of air travel by users with disabilities has been accompanied by several challenges regarding the overcoming of barriers that obstruct the full use of these airport environments, and, to meet the demand of these passengers, there are Brazilian standards, such as Resolution No. 280, 2013, of the National Civil Aviation Agency, as well as international regulations, such as the U.S. Federal Code14 CFR Part 382 (Air Carrier Access Act), which was issued in 1987, and its amendments, and the European, through the Regulation No. 1107/2006 (European Union) of accessibility, which aims to provide and guide the conditions for the independent use, safely and autonomously. The aim of the research was to verify the existence of gaps in these regulations regarding the effectiveness of the inclusion of these users with disabilities in the air travel process, abstracted through a qualitative metasynthesis of the concepts of people with disabilities and accessibility (which refers to environmental and social contexts), subsidizing the analysis of these regulations, as well as proposing improvements to these analyzed regulations. The results of the qualitative meta-synthesis point out that the current concepts of the person with disability and accessibility are elements which comprise the same discussion spectrum, that is, one correlates with the development of the other, for the person with disability is only "disabled" when the environment does not propose elements susceptible of full accessibility by means of the principles designated by the universal design. In the analysis of these concepts abstracted from the meta-synthesis with the standards, as well as the discussion about them, it was verified that they present frailties in relation to the criteria of environment transformation by the accessibility of the universal design, so that the disability which, before, was established as a person's infirmity, disappears when the person can have full access to these environments, being socially inclusive. The barriers imposed in the air travel process are complex and interact with all the parties and the several players in the air travel process, thus making the uses of these spaces more challenging for passengers with disabilities, and a standard that serves as a guide is required to solve all these obstacles, with the change being based on the environment, and not on the conduct of these passengers. By this premise, the improvement of the norm consists, in a first moment, in separating the prescriptions that mention the improvement of the environment in the sense of offering a universalization of accessibility from the medical situations of illness that the passengers have. This dichotomy resides in specifying situations in which the passenger's capacity is compromised due to illnesses that require specific care, to be treated in separate norms, including with the support of the regulatory health and sanitary surveillance bodies. Therefore, the whole effort of the research is relevant for the inclusion of people with disabilities in the several social contexts, especially in the passenger air transport, being that the norm is, at the same time, a regulated situation, in the sense of imposing a formalization of the situations. On the other hand, it cannot be understood only by reasons of its formal interlacing, being plausible to be modified due to the evolution of science and its precepts that are comprehended therein.
Analysis of accessibility standards in air transport: a discussion by through a qualitative meta-synthesis of the concept of people with disabilities and the accessibility
Keywords: Pessoa com deficiência; Transporte aéreo de passageiros; Acessibilidade; Normas; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DA PRODUCAO; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::PLANEJAMENTO EM CIENCIA E TECNOLOGIA; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE SETORES ESPECIFICOS; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO::PROJETO DE ARQUITETUTA E URBANISMO; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO::TECNOLOGIA DE ARQUITETURA E URBANISMO; CIENCIAS DA SAUDE::ENFERMAGEM; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO; ENGENHARIAS::ENGENHARIA AEROESPACIAL::ESTRUTURAS AEROESPACIAIS; ENGENHARIAS::ENGENHARIA AEROESPACIAL::PROPULSAO AEROESPACIAL; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::ERGONOMIA; ENGENHARIAS::ENGENHARIA AEROESPACIAL; ENGENHARIAS::ENGENHARIA DE PRODUCAO; ENGENHARIAS::ENGENHARIA DE TRANSPORTES; ENGENHARIAS::ENGENHARIA AEROESPACIAL::ESTRUTURAS AEROESPACIAIS::PROJETO DE ESTRUTURAS AEROESPACIAIS